CV Entanglement Analysis in the Superposition of Subharmonic and Second Harmonic Generation of Light with Injected Squeezed Laser Beams (Global Journal of Science Frontier Research, 2017)
In this article, we have analyzed the squeezing and statistical properties of the light generated by the superposition of second harmonic light and degenerate three level squeezed laser beams. We have found that the mean photon number of the superposed light beams to be the sum of the mean photon number of that of the constituent light beams. However, the photon number variance of the superposed light beams does not happen to be the sum of the photon number variances of the separate light beams. On the other hand, the quadrature variance of the superposed light beams is the sum of the individual light beams. Furthermore, we have observed that the degree of squeezing for the superposed light beams is the average of the segregate light beams and the degree of squeezing is approximately 53.95% below the coherent state level. Even though, we have verified that the superposition of subharmonic and second harmonic light with injected degenerate three-level laser beams he haves squeezing, we do not show continuous variable entanglement. But, the absence of the laser beam in the superposition state give rise entangled photons.
Keywords: CV; entanglement; Q function; squeezing